Revolution solids with GeoGebra: Sólidos de revolución con GeoGebra - Vergara Ibarra, José Luis (2021)
This paper shows how to design revolution solids with GeoGebra software. First in each section the relevant definitions are given for this purpose, after this the curves are parameterized at ℝ3 and the surface bounded by these curves, finally by commands and sliders the solid of revolution is obtained. The solids obtained are dynamic and can be represented in different perspectives